Chemistry the central science - Brown, Theodore L.; LeMay, H. Eugene; Bursten, Bruce E.; Murphy, Catherine J.; Woodward, Patrick M.; Stoltzfus, Matthew; George, Adrian V.; Langford, Steven J.; Lufaso, Michael W. (Harlow, Esses, UK Pearson, 2022)
"Publishing the fifteenth edition of this text bespeaks an exceptionally long record of successful textbook writing. We are appreciative of the loyalty and support the book has received over the years, and we are mindful of our obligation to justify each new edition. We begin our approach to each new edition with an intensive author retreat in which we ask ourselves the deep questions that we must answer before we can move for-ward. What justifies yet another edition? What is changing in the world not only of chemistry, but with respect to science education and the qualities of the students we serve? How can we help your students not only learn the principles of chemistry, but also become critical thinkers who can think more like chemists? The answers lie only partly in the changing face of chemistry itself. The introduction of many new technologies has changed the landscape in the teaching of sciences at all levels. The use of online resources in accessing information and presenting learning materials has markedly changed the role of the textbook as one element among many tools for student learning. Our challenge as authors is to maintain the text as the primary source of chemical knowledge and practice, while at the same time integrating it with the new avenues for learning made possible by technology. This book incorporates a number of technologies to improve pedagogy, including use of computer-based classroom tools, such as Mastering Chemistry, which is continually evolving to provide more effective means of testing and evaluating student performance, while giving the student immediate and helpful feedback. Video feedback for a select number of Exam Prep questions is also available in Mastering Chemistry, which is new to this edition"-- Provided by publisher.
Includes index.
15th Global edition in SI units.
"Global edition" -- Cover page.
Authorized adaptation from the United States edition: Chemistry: the central science / Theodore L. Brown [and five others]. -- Fourteenth edition. -- 2018.
Keywords: Chemistry -- Textbooks